Dosage Derivation of Marbofloxacin in Broiler Chickens based on Pharmacokinetic-Pharmacodynamic Integration - Singh, Ratn Deep; Sanjay H. Vaghela; Tukra, Sheen; Patel, Ankit R.; Patel, Hitesh B.; Sarvaiya, Vaidehi N.; Mody, Shailesh K. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Marbofloxacin, a veterinary–exclusive antimicrobial drug of third–generation fluoroquinolone class, exhibits wide spectrum antimicrobial activity against Gram-negative as well as Gram-positive bacteria, and thus, is a promising agent to treat susceptible bacterial infections in poultry. Therefore, the present study was conducted to derive dosage regimen of marbofloxacin based on the results of intravenous and oral pharmacokinetic (PK) trial in sixteen healthy broiler chickens. Plasma concentrations of marbofloxacin were measured by optimized and in-house validated Ultra High Performance Liquid Chromatography (UHPLC) method. The PK parameters were calculated from plasma concentrations versus time data by non-compartmental analysis using ‘PK Solver 2.0’ software. Following oral administration of marbofloxacin at the dose rate of 5 mg/kg body weight, the mean maximal plasma concentration (Cmax: 2.193 µg/ml) was achieved at 1.68 h. Marbofloxacin showed long half-life (6.03 h), high volume of distribution (2.64 L/Kg) and good oral bioavailability (88.10 %). The average plasma concentration of marbofloxacin ≥ 0.32 µg/ml was maintained upto 12 h and 0.10 µg/ml at 24 h. Based on the values of PK-PD integrated indices, it is concluded that oral dose of marbofloxacin @ 5.0 mg/kg body weight, to be repeated at 24 h, would be efficient to treat common bacterial pathogens of broiler chickens having MIC ≤ 0.12 μg/ml.